Jointness in torts; comparative study in US and Iranian law emphasizing the concept of attribution - hamed najafi; mahmoud sadeghi; morteza shahbazinia (پژوهش‌نامه حقوق اسلامی, 2020)
Joint tortship in its general sense is the intervention of more than one personin committing tort. In this sense, the jointness acompanicity and participatesin it. The jointness, in a special sense, is limited to interfere more than twopersons in the commission of the operation and the material element of thetort. In the US legal system, in addition to cases where two or more peoplereally commit actus reus of tort, there are instances where with use of titlessuch as "attribaution", commition of actus reus is attributed to more than oneperson, Virtually. In this legal system, this is based on goals such as redressand deterrence. In Iranian law, according to the well-known Opinion, thejointness in tort, is subject to the commission of actus reus by two or morepersons and apparently in some cases, like the American law, with implicitusing of the title "attribution", realization of jointness in tort is ruled thatdoes not look right. Because, contrary to the US law and some veiws inpopular jurisprudence, when the legislator in the latter part of Article 535 ofthe Islamic Penal Code of 2013 considers intent to have an impact on thematerial reality of the jointness, he does not abide by all its effects andassumption. In the case of criminal responsibility, it imposes the lesspunishment on the accomplice and in the case of civil liability, he assumesthe distribution of damages on multiple causes. In the present study, it hasbeen proved by a descriptive-analytical method that, unlike the US lawwhich because of its instrumentalist nature, jointness in wrongs has widescope, in Iranian law, because of its ethical basis, jointness in wrongs, hasnarrow scope and Accordingly, it is proposed to amend or delete the last partof Article 535 of the Islamic Penal Code of 2013